Islamic Marketing Management at Sofyan Kalimas Hotel and Namira Syariah Hotel in Surabaya - Abdul Mujib; Rukhul Amin (Journal of Islamic Economics (JoIE), 2024)
Introduction: Currently, the halal tourism business through sharia hotels is increasingly vibrant in the era of globalization in line with the large demand for domestic and foreign halal tourism markets. Islamic marketing is an important part in developing the halal industry in the hotel sector, in addition to sharia compliance in sharia hotels. The purpose of this research is to analyze sharia hotel marketing management: case studies at Sofyan Kalimas Hotel and Namira Hotel in Surabaya, East Java, Indonesia. Research Methods: This research uses a case study approach with a descriptive qualitative research type the researcher will directly engage in fieldwork to conduct observations and data collection. The data will be sourced from both primary and secondary data. Data collection techniques will include interviews with several informants, observations and documentation. The analysis process will begin with data collection, followed by data reduction to select key information, presentation of the data, and finally drawing conclusions. Result: The research results show that sharia hotel marketing management in stills religious values by emphasizing norms, attitudes and behaviour by applying Islamic principles, Islamic practices, Islamic rules and Islamic beliefs, both internal and external management. In internal marketing as a differentiator from conventional hotels, it adds the Islamic atmosphere variable and externally it adds Islamic brotherhood. Conclusion: Then, to improve marketing, hotel management must build relationships and collaborate with stakeholders, including the government, institutions, Islamic mass organizations which are marketing targets.